Analysis of the influence of properties management in the region on the transaction prices level of unbuilt land properties – case study - Mika, Monika; Siejka, Monika; Leń, Przemysław (International Conference “Environmental Engineering”, 2017)
This article presents the results of analysis of the influence of selected economic, legal and environmental factors on the level of transaction prices of unbuilt land properties, in two randomly selected districts of the southern Poland. The results of the research allowed extraction of a group of factors influencing the spatial distribution of the average prices of the surveyed properties. They gave also the answer to the question about the extent to which the unit prices are confirmed by the state of properties management in the region. An analysis of the existing state in the selected region based on the analysis of the local market was performed. Furthermore, the conformity of local plans for the studied areas was examined, as well as an analysis of spatiotemporal distribution of transaction prices of real estate was performed. The research has shown that the level of transaction prices on the local real estate markets is related to the real estate management of the surveyed areas. The state of the economy is affected by many factors, most important of which seems to be the location in relation to urban areas and the condition of the access roads. The undertaken tests correspond with the directions of the world research.